MARYAM NAWAZ’S PRESS CONFERENCES ON THE RECENT FLOODS IN PUNJAB, PAKISTAN: A CRITICAL DISCOURSE ANALYSIS (Contemporary Journal of Social Science Review, 2025)
Natural disasters like floods are not only problems of nature, but they also become important moments for political leaders to communicate with the public. During such times, people expect leaders to show responsibility, care, and good decision making. Language plays an important role in how people understand the situation and trust their leaders. This study looks at the press conferences given by Maryam Nawaz during the recent floods in Punjab, Pakistan, using Critical Discourse Analysis (CDA). The study follows a qualitative research method and analyzes five official press conferences that were held at different times of the flood crisis. Relevant statements about floods were selected through purposive sampling to focus on leadership and crisis communication. Using Fairclough’s three-dimensional model, the study examines language features like word choice, use of pronouns, repetition, and overall tone. The analysis shows how ideas of leadership, responsibility, and empathy are presented through language. The findings suggest that Maryam Nawaz often uses inclusive and strong language to highlight government efforts, public welfare, and administrative duties. Her speech tries to show a positive image of governance by mixing sympathy for people with firm decision making.